Using crossmodal correspondences as a tool in wine communication - Crichton-Fock, A; Spence, C; Pettersson, N (Frontiers Media, 2023)
Introduction: This research investigates consumer acceptance of alternative methods for communicating information about wine, focusing on the alignment between sensory attributes and consumer expectations. Methods: A survey was administered to wine enthusiasts to assess their attitudes toward crossmodal communication. Results: The findings reveal significant associations between consumer behaviors and acceptance of alternative communication methods, highlighting the emerging field of crossmodal correspondences. Discussion: These results suggest that leveraging crossmodal correspondences can enhance the match between a product’s sensory qualities and consumer expectations, potentially reducing wine wastage resulting from unmet consumer preferences. These findings have implications for improving communication strategies in the wine industry and enhancing consumer experiences.